Answer:
46
Step-by-step explanation:
You need just substitute values of x and y, and calculate.
24x - 13y = 24*3 - 13*2 = 72 - 26 = 46
The equation is <span>f(x) = 2x5 - 9x4 + 12x3 - 12x2 + 10x - 3 = 0
remark:
the sum of coefficients is = 2-9+12-12+10-3=-7+7=0, so a=1 is a zero of f
f can be written as </span>f(x) = (x-1)Q(x), and f(x) / (x-1)= Q(x)
after euclid's division
Q(x) = 2x4 - 7x3 + 5x2 - 7x +3
so for finding the other roots, making Q(x) for product of factors is a must
Answer:
Answer:
The width is 4 units, and the length is 10 units.
Step-by-step.
Step-by-step explanation:
area of rectangle = length * width
Let L = length; let W = width.
"The length is 6 units greater than the width.": L = W + 6
area = LW = 40
Since L = W + 6, we substitute L with W + 6.
(W + 6)W = 40
W^2 + 6W = 40
W^2 + 6W - 40 = 0
(W - 4)(W + 10) = 0
W - 4 = 0 or W + 10 = 0
W = 4 or W = -10
A width cannot be a negative number, so we discard the solution W = -10.
W = 4
L = W + 6 = 4 + 6 = 10
The width is 4 units, and the length is 10 units.
The correct question is:
Suppose x = c1e^(-t) + c2e^(3t) a solution to x''- 2x - 3x = 0 by substituting it into the differential equation. (Enter the terms in the order given. Enter c1 as c1 and c2 as c2.)
Answer:
x = c1e^(-t) + c2e^(3t)
is a solution to the differential equation
x''- 2x' - 3x = 0
Step-by-step explanation:
We need to verify that
x = c1e^(-t) + c2e^(3t)
is a solution to the differential equation
x''- 2x' - 3x = 0
We differentiate
x = c1e^(-t) + c2e^(3t)
twice in succession, and substitute the values of x, x', and x'' into the differential equation
x''- 2x' - 3x = 0
and see if it is satisfied.
Let us do that.
x = c1e^(-t) + c2e^(3t)
x' = -c1e^(-t) + 3c2e^(3t)
x'' = c1e^(-t) + 9c2e^(3t)
Now,
x''- 2x' - 3x = [c1e^(-t) + 9c2e^(3t)] - 2[-c1e^(-t) + 3c2e^(3t)] - 3[c1e^(-t) + c2e^(3t)]
= (1 + 2 - 3)c1e^(-t) + (9 - 6 - 3)c2e^(3t)
= 0
Therefore, the differential equation is satisfied, and hence, x is a solution.